Still my Grandma - Abeele, Veronique van den.; Dubois, Claude K. (Grand Rapids, Mich. : Eerdmans Books for Young Readers, 2007)
A young girl describes her special relationship with her grandmother, both before and after Grandma contracts Alzheimer's Disease.
Keywords: Grandmothers -- Juvenile fiction; Alzheimer's disease -- Juvenile fiction; Grandmothers -- Fiction; Alzheimer's disease -- Fiction; Alzheimer's disease; Grandmothers; Fiction; Juvenile works